The Role and Contribution of Inclusiveness of Taklim Assembly, Growing Multicultural, Egalitarian and Religious Society - Maisaroh, Ima; Muhyidin , Asep; Jamaludin, Ujang; Jakaria, Jakaria; Burhanuddin (Indonesian Journal of Social Science Research, 2025)
Majelis Taklim, as a non-formal religious education institution, plays an important role in strengthening social harmony in Indonesia, which is rich in ethnic, religious and cultural diversity. This institution not only spreads Islamic teachings, but also promotes the values of tolerance, equality, and moderate religiosity to build an egalitarian and harmonious multicultural society, amidst the challenges of intolerance and social polarization. This research aims to analyze the role and contribution of Majelis Taklim in fostering an egalitarian and religious multicultural society, as well as its relevance in answering modern challenges such as radicalism and lack of technological literacy. The research uses a qualitative approach with literature analysis of various studies related to Majelis Taklim, such as the works of Jamil et al. (2023)[11], Huda (2016)[6], and Sagala (2019). Data were collected from field research, government regulations, and reports of Majelis Taklim activities in various regions, analyzed thematically to identify its inclusive role and barriers. Research Results: Majelis Taklim, such as Intan Raudah in Garut and Al-Hidayah in Lampung, successfully promote tolerance through interfaith dialogue, socio-economic empowerment, and moderate education, reduce religious-based conflicts, and increase social cohesion. However, challenges such as non-standardized curriculum and low technological literacy need to be addressed through training and innovation. Research Benefits: This research provides practical recommendations to strengthen the role of Majelis Taklim as agents of multicultural education and social harmony, supporting inclusive education policies and equitable community development.